The complexity of tone in Nubri - Donohue, Cathryn; Donohue, Mark (Nepalese Linguistics, 2019)
This paper introduces the tonal system of the amagaun dialect of Nubri. We first present an introduction to linguistic tone, with a focus on tone as it is found in Tibetan languages, before moving on to describe the tones in Samagaun Nubri monosyllables and disyllabic expressions. We conclude that the tonal system in Nubri cannot be accounted for by exclusive reference to Tibetan languages. The implication is that contact with a non-Tibetan language has played a significant role in the history of the language.